2019
DOI: 10.1364/ol.44.004267
|View full text |Cite
|
Sign up to set email alerts
|

Single-step fabrication of surface waveguides in fused silica with few-cycle laser pulses

Abstract: Direct laser writing of surface waveguides with ultrashort pulses is a crucial achievement towards all-laser manufacturing of photonic integrated circuits sensitive to their environment. In this Letter, few-cycle laser pulses (with a sub-10 fs duration) are used to produce subsurface waveguides in a non-doped, non-coated fused silica substrate. The fabrication technique relies on laser-induced microdensification below the threshold for nanopore formation. The optical losses of the fabricated waveguides are gov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…12,13 A recent trend in ultrashort laser processing relies on the use of few-cycle pulses, predicted to achieve ultimate precision, thus preparing a new generation of micro-processing tools. 14,15 They enable an extended processing control by tuning the interplay between multiphoton excitation and strong field ionization, 16 where the cycling of the laser pulse becomes critical.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A recent trend in ultrashort laser processing relies on the use of few-cycle pulses, predicted to achieve ultimate precision, thus preparing a new generation of micro-processing tools. 14,15 They enable an extended processing control by tuning the interplay between multiphoton excitation and strong field ionization, 16 where the cycling of the laser pulse becomes critical.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation with the corresponding coherent EM promotes these EPs to an arbitrary order in the emerging synthetic coupled structure in the N$N$‐photon Fock‐space, and this without the need of further fine‐tuning of the loss‐rates in the underlying physical system. [ 44 ] Utilizing PNR detectors, it is then possible to exploit the effect of loss‐induced transparency in the quantum optical regime. We have outlined this concept for the semi‐lossy waveguide beamsplitter, which is excited by its coherent exceptional mode.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we have shown that arrays of coupled waveguides exhibiting alternating patterns of lossy and lossless sites, gives rise to several EPs of second order at the single photon or, equivalently, the classical level. The excitation with the corresponding coherent EM promotes these EPs to an arbitrary order in the emerging synthetic coupled structure in the N -photon Fock-space, and this without the need of further fine-tuning of the loss-rates in the underlying physical system [41]. Utilizing PNR detectors, it is then possible to exploit the ef-fect of loss-induced transparency in the quantum optical regime.…”
Section: Discussionmentioning
confidence: 99%